Open Access, impact and quality: an even harder future for gatekeepers? (Epidemiology, Biostatistics, and Public Health, 2022)
With the advent of open access publishing, coupled with easy electronic access to journals, many of the historical constraints towards access to the litterature – both as an author and as a reader – have recently been reshaped, and are still changing, raising among others issues about the quality of what is published. Many aspects are being looked at very carefully, but so far the role of the media has only occasionally been investigated. On one side, more and more scholars oppose the current use of...